Analysis of Placement and Rating Selection of Lightning Arresters for 20 kV Distribution Networks - A Case Study - Arlenny Arlenny; Aj Pandapotan Silalahi; Masnur Putra Halilintar; Mahmud Akhyar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
Disturbances caused by lightning strikes in the electric power system may occur in the transmission and distribution area. This paper aim is to analysis of placement and rating selection of lightning arresters for 20 kV distribution networks. A case study was conducted in the network assets of PT. PLN (Persero) at the Maroko feeder, Rayon Duri, Indonesia. This study method employed a quantitative analytical approach to evaluate the optimal placement and rating selection of 5 kA and 10 kA distribution-class lightning arresters within the 20 kV network of PT. PLN (Persero) Rayon Duri. The results of placement and arrester rating for the Maroko feeder revealed the voltage rating specification of 19.2 kV and a current of 10 kA. It was expected that the arrester can minimize lightning strike disturbances that cause induction. The results obtained after conducting simulations, the arrester can reduce a fairly large voltage quickly with a distance of 5.6334 meters from the disturbance and the duration of 1.2 - 50 ?s. Therefore, placing the arrester in close proximity to the equipment significantly improves insulation coordination by accelerating the suppression and safe discharge of lightning-induced surges.